A current-reuse biomedical amplifier with a NEF < 1 - Miguez, Matías R. (2018)
Noise Efficiency Factor (NEF) is the most employed figure of merit to compare different low-noise biomedical signal amplifiers, taking into account current consumption, noise, or bandwidth trade-offs. A small NEF means a more efficient amplifier, and was assumed to be always NEF > 1 (an ideally efficient single BJT amplifier). In this work current-reuse technique will be utilized to exceed this limit in a very efficient CMOS amplifier. A micro-power, ultra-low-noise amplifier, aimed at electro-neuro-graph signal recording in a specific single-channel implantable medical device, is presented. The circuit is powered with a standard medical grade 3.6 V(nom) secondary battery. The amplifier input stage stacks twelve differential pairs to maximize current-reuse. The differential pair stacking technique is very efficient: allows most of the energy to be dissipated in the input transistors that amplify and not in mirror or bias transistors, and allows also the input transistors to operate with a reduced VDS just above saturation. The amplifier was implemented in a 0.6 μm technology, it has a total gain of almost 80 dB, with a 4 kHz bandwidth. The measured input referred noise is 4.5 nV/Hz1/2@1 kHz, and 330 nVrms in the band of interest, with a total current consumption of only 16.5 μA from the battery (including all the 4 stages and the auxiliary circuits). The measured NEF is only 0.84, below the classic NEF = 1 limit.